Antioxidant Capacity of Sulfated Polysaccharides from Seaweeds. a Kinetic Approach - Encina-Rojas, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Chandia-Parra, N (2011)
The antioxidant capacity of sulfated galactans from Gigartina skottsbergii and Schizymenia binderi, commercial carrageenans, and fucoidan from Lessonia vadosa was evaluated by the oxygen radical absorbance capacity (ORAC) method using fluorescein and c-phycocyanin as target molecules. Even though, relative ORAC values for sulfated galactans are similar for both employed probes, they are higher for fluorescein. Results of antioxidant capability are analyzed in terms of the structural parameters of polysaccharides. Fucoidan, from the brown seaweed L. vadosa and the sulfated galactan from the red seaweed, S. binderi exhibit the highest antioxidant capacity by the ORAC method. Although, the ORAC assay is not used to evaluate the quenching of peroxyl radicals by polysaccharides, we demonstrated that this method constitutes an adequate assay for evaluating the antioxidant capacity of aqueous soluble polysaccharides. The antioxidant capacity was also evaluated by ABTS and hydroxyl radical scavenging assays. The kinetic profiles for the reaction of ABTS+ with polysaccharides display a fast initial reaction kinetics followed by a slow component. Antioxidant activity, obtained from the end of the fast kinetic, was higher for fucoidan and sulfated galactan from S. binderi than for commercial carrageenans. The reaction of the polysaccharides with hydroxyl radicals is complex. Kinetics studies showed a fast reaction followed by a slower reaction that leads polysaccharide derived radicals to inhibit the antioxidant activity. © 2010 Elsevier Ltd.